Use of periodicals in the Filipiniana and Special Collections Division, University of the Philippines, Diliman Main Library, June 1987 to September 1988 - Ponseca, Zenaida R.; Faderon, Rosalie B.; Arlante, Salvacion M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1990)
The study was conducted to: 1) find out the categories of users who have a great demand for various types of periodicals; 2) determine what percentage of the entire periodical collection is frequently used; 3) identify which of the existing periodical titles in the Filipinina collection are frequently requested by the users; and 4) identify the topics/subjects frequently read/inquired into them.
The descriptive method of research was used in the study. Used periodical call slips were collected and analyzed. Tables showing percentages and rankings were used in the analysis and interpretation of data.
The findings reveal that out of 11,785 requests made, the students are the number one users of the periodicals with 11,157 (94.67 percent) of the total requests. Undergraduates from the College of Social Sciences and Philosophy ranked number one with 2,341 requests among the colleges/units.
The academic non-teaching staff ranked second among the users of the periodicals with 220 (1.9 percent).Periodicals published during the last three years (1986-1988) were mostly requested. Popular and current periodicals published weekly were the most requested in the first fifty periodical titles most frequently used. Philippine Panorama ranked number one (926 or 7.86 percent).
The most requested topics of inquiry are in the major fields of the social sciences such as political science, history, sociology, folklore, customs and costumes, and economics. In the humanities, the most requested topics of inquiry are literature, and theater/performing arts.
Based on the findings of the study, the following recommendations are made to improve the services rendered in the periodical collection of the Filipiniana and Special Collections Division of the University of the Philippines Diliman, Main Library: 1) a study be undertaken on why there have been few faculty members who used the periodical collection; 2) further study on the use of periodical literature be undertaken among the students of the College of Mass Communication; 3) periodical titles that have not been indexed be sent to the Bibliography and Indexing Division for indexing and for the Bibliography and Indexing Division to undertake a review of their internal policies and guidelines regarding indexing; 4) a review of the Index to Philippine Periodicals be undertaken to determine which periodical titles have been/are indexed; 5) the less or least used periodical titles are well as those with no lending activity should be temporarily relocated to a nearby storage area to give way to most frequently used titles; and 6) the Division's staff be given ample time to be well informed on current issues.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman). -- Library. -- Filipiniana and Special Collections Division; Periodicals -- Use studies; Periodicals -- Circulation